Neuro-WiFi: Will It Be an Icebreaking Target for Neurological Diseases? - Pinto, Josué (Science Insights, 2023)
With the progress of neuroscience, there is a growing curiosity and conjecture surrounding neuro-WiFi and its potential influence on neurological diseases. The concept of neuro-WiFi, which entails wireless communication between neurons in the brain, has the potential to profoundly transform our comprehension of brain function and create novel opportunities for therapy. Nevertheless, like any revolutionary technology, there are apprehensions regarding potential targets for neurological illnesses. Wireless communication networks in the brain may create an avenue for malevolent individuals to exploit weaknesses and obtain unauthorized access to neural data. The utilization of neuro-WiFi generates apprehensions regarding privacy, security, and ethical implications. As thus, it is essential to establish strong controls and processes to assure its safe use, in order to optimize its advantages while avoiding any risks related to targeting neurological diseases.